Numerical approximation of a nonlinear parabolic partial differential equation - Bhowmik, Samir K. (BRAC University, 2010)
We consider the Allen-Cahn model of phase transitions. We approximate the problem using finite difference method in space coupled with several explicit and implicit methods in time and compare the solutions. We present some numerical experimental results of such approximations.